Engaging learners with complex learning difficulties and disabilities a resource book for teachers and teaching assistants - Carpenter, Barry; Egerton, Jo; Cockbill, Beverley; Bloom, Tamara; Fotheringham, Jodie; Rawson, Hollie; Thistlethwaite, Jane (Routledge, 2015)
"Children and young people with Complex Learning Difficulties and Disabilities (CLDD) have co-existing and overlapping conditions which can manifest in complex learning patterns, extreme behaviours, and a range of socio-medical needs which are new and unfamiliar to many educators. Their combination of issues and layered needs - mental health, relationship, behavioural, physical, medical, sensory, communication and cognitive - mean they often disengage from learning, and challenge even our most experienced teachers. This book provides school practitioners and leaders with an approach and resources to engage this often disenfranchized group of children in learning. The Engagement for Learning Framework has been developed and trialled by over 100 educational settings (both special and mainstream) with learners from early years to post-16. It gives practitioners from a range of disciplines a shared means of assessing, recording, developing personalized learning pathways and demonstrating progression for these children. The focus on inquiry means that however complex a young person's needs, educators will be able to apply the approach. This practical and engaging book provides literature, tools and case study examples outlining who children and young people with CLDD are, why their engagement for learning is important, and how the Engagement for Learning Framework can be used effectively by teachers and other professionals to ensure the best possible outcomes for these children"--Provided by publisher.